Sugar-Sweetened Beverages Consumption among College Students: The Role of Fear of Missing Out - Permatasari, Riasyah; Muslihah, Nurul; Rahmawati, Widya (Indonesian Journal of Human Nutrition, 2026)
Sugar-sweetened beverages (SSBs) have become an important component of dietary patterns associated with weight gain and metabolic disorders among adults. SSB consumption may be influenced by various internal and external factors, including psychological factors such as Fear of Missing Out (FoMO), which may contribute to impulsive purchasing behaviors involving food and beverages. The primary objective of this study was to investigate the differences in Fear of Missing Out levels and sugar-sweetened beverage (SSB) consumption frequency between college students enrolled in health-related and non-health-related study programs. This research used a cross-sectional design. A total of 423 female respondents were selected using a self-selection sampling method. The results indicated differences in sugar-sweetened beverage consumption between health and non-health students. Respondents with a high category of FoMO were at risk of consuming SSBs at a higher frequency. Variations in sugar content and consumption patterns were also identified across different beverage types, and students from non-health-related programs consumed more SSBs than students from health-related programs. These findings indicate the need for nutritional interventions in this group to reduce health risks associated with excessive sugar-sweetened beverages consumption.